2021
DOI: 10.3390/metabo11120799
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and Male Fertility: A Dangerous Crosstalk

Abstract: In recent decades, an increasing incidence of male infertility has been reported. Interestingly, and considering that pesticides have been used for a long time, the high incidence of this pathological state is concomitant with the increasing use of these chemicals, suggesting they are contributors for the development of human infertility. Data from literature highlight the ability of certain pesticides and/or their metabolites to persist in the environment for long periods of time, as well as to bioaccumulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…These findings resulted from oxidative damage caused by an increment in MDA and NO levels, as well as a decrement in antioxidant enzyme activity (Saleh et al, 2020). We suggest that the germ cell death occurred via the intrinsic mechanism, also known as the mitochondrial pathway, resulting from an oxidative stress injury in this organelle, which was consistent with previous findings (Mohamed et al, 2019; Moreira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings resulted from oxidative damage caused by an increment in MDA and NO levels, as well as a decrement in antioxidant enzyme activity (Saleh et al, 2020). We suggest that the germ cell death occurred via the intrinsic mechanism, also known as the mitochondrial pathway, resulting from an oxidative stress injury in this organelle, which was consistent with previous findings (Mohamed et al, 2019; Moreira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Androgen hormone disruption, particularly testosterone, changed the function, histology, and morphometry analyses of reproductive organs such as the testes, epididymis, prostate gland, ductus deferens, seminal vesicle, ovary, and uterus, as well as caused changes in organ weight (Tehrani et al, 2013; Yusoff et al, 2021). Testosterone is produced by Leydig cells, which is required for spermatogenesis, sperm maturation, sexual performance in individuals, and the masculinization of the male foetus development (Moreira et al, 2021; Wang et al, 2017). Sertoli cells provide optimal care as a fuel source for progenitor cell maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the present study found that the pesticide mixture was associated with decreasing levels of LH, a key regulator of spermatogenesis initiation and maintenance (Moreira et al, 2021). This association could be explained based on the negative-feedback mechanism on the HPG axis.…”
Section: Tablesupporting
confidence: 45%
“…However, whether effect could be produced centrally, as observed for BPA, remains unknown. Secondly, by external interaction with Leydig cells, which decreases T circulating levels and activates the release of kisspeptin through the negative feedback triggered by the hypothalamic-pituitary-testicular (HPT) axis (Babakhanzadeh et al, 2020;Moreira et al, 2021). In this regard, dimethoate-exposed Leydig cells of male rats led to decreased T levels (Babakhanzadeh et al, 2020).…”
Section: Tablementioning
confidence: 99%